Did the Massachusetts healthcare reform make people happier? - KIM, Seonghoon (Institutional Knowledge at Singapore Management University, 2018)
We study the effects of Massachusetts’ healthcare reform on individuals’ subjective well-being. Using data from the Behavioral Risk Factor Surveillance System, we find that the reform significantly improved Massachusetts residents’ overall life-satisfaction. This result is robust to various sensitivity checks and falsification tests. We find consistent evidence from other healthcare reforms such as the 2014 Affordable Care Act Medicaid expansion and the 2005 Tennessee Medicaid disenrollment, supporting our findings’ external validity. Our results provide novel evidence on the psychological consequences of recent healthcare reforms expanding health insurance coverage to the uninsured.